2014
DOI: 10.1149/2.002407jes
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Composition and Corrosion Resistance of Zn-Ni-P Alloys Electrodeposited from an Ionic Liquid Based on Choline Chloride

Abstract: Ternary Zn–Ni–P alloy coatings were electrodeposited from electrolytes based on choline-chloride ionic liquid. Their phases, microstructures, chemical compositions and corrosion behaviors were characterized as a function of electrodeposition current density. Varying the deposition current density has an influence on the composition and corrosion resistance of the obtained amorphous Zn-Ni-P deposit. The chemical composition results show that during electrodeposition from ionic liquids, P is incorporated into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This was reported for single metal coating (such as Ni [76]) and multi-ingredient coating (such as Ni/MWCNT composite [77], Co-Sn alloy [78], Ni-P alloy [79], Zn-Ni-P [80] and Mg-Nd-Zn-Zr alloy [81]). DES electrolytes have offered a flexibility to obtain several film compositions for different coating purposes.…”
Section: Des-based Nano Production: An Overview About Applications Amentioning
confidence: 71%
“…This was reported for single metal coating (such as Ni [76]) and multi-ingredient coating (such as Ni/MWCNT composite [77], Co-Sn alloy [78], Ni-P alloy [79], Zn-Ni-P [80] and Mg-Nd-Zn-Zr alloy [81]). DES electrolytes have offered a flexibility to obtain several film compositions for different coating purposes.…”
Section: Des-based Nano Production: An Overview About Applications Amentioning
confidence: 71%
“…The second phase (2014–2018) is the transformation burst stage, and the burst keywords that grow steadily in this stage are deposition, media, contact, and solubility . This stage belongs to the rapid variation period, and there is more research literature related to ionic liquid corrosion inhibition in this stage.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The first stage (2011–2013) is the predevelopment stage. The burst words in this stage were electrophoresis, corrosion, , aluminum, and alloy. The burst keywords in this stage lasted for a long time, so it was considered that this stage provided the basis for the study of subsequent research.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was easy to tune the morphology, composition and phase structure of ZnCo alloys by adjusting the deposition potential. In another work by Fashu and coworkers, it was found that the electrodeposition of ZnNiP in choline chloride‐based DES also followed a normal codeposition mechanism. The composition, morphology and corrosion resistance of ZnNiP deposits depended on current density.…”
Section: Direct Electrodeposition From Ilsmentioning
confidence: 95%